2021
DOI: 10.2196/25392
|View full text |Cite
|
Sign up to set email alerts
|

A Transdiagnostic Self-management Web-Based App for Sleep Disturbance in Adolescents and Young Adults: Feasibility and Acceptability Study

Abstract: Background Sleep disturbance and its daytime sequelae, which comprise complex, transdiagnostic sleep problems, are pervasive problems in adolescents and young adults (AYAs) and are associated with negative outcomes. Effective interventions must be both evidence based and individually tailored. Some AYAs prefer self-management and digital approaches. Leveraging these preferences is helpful, given the dearth of AYA treatment providers trained in behavioral sleep medicine. We involved AYAs in the co-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…There is robust evidence indicating that self-guided web-based CBT-I produces similar effect sizes for improving insomnia symptoms in adults compared to face-to-face CBT-I [ 68 ], although similar data in youth are lacking. Recently, Carmona and colleagues [ 69 ] demonstrated feasibility and acceptability of a transdiagnostic web-based app for adolescents and young adults (AYAs), which provides self-guided training in sleep education, personalized feedback comparing the user’s sleep patterns to age-based norms, and tailored goal setting to improve sleep habits. We are not aware of any published randomized controlled trials testing technology delivered sleep health interventions for youth, although studies are currently underway (e.g., [ 70 ]).…”
Section: Interventions To Improve Sleep Health In Pediatric Pain Popu...mentioning
confidence: 99%
“…There is robust evidence indicating that self-guided web-based CBT-I produces similar effect sizes for improving insomnia symptoms in adults compared to face-to-face CBT-I [ 68 ], although similar data in youth are lacking. Recently, Carmona and colleagues [ 69 ] demonstrated feasibility and acceptability of a transdiagnostic web-based app for adolescents and young adults (AYAs), which provides self-guided training in sleep education, personalized feedback comparing the user’s sleep patterns to age-based norms, and tailored goal setting to improve sleep habits. We are not aware of any published randomized controlled trials testing technology delivered sleep health interventions for youth, although studies are currently underway (e.g., [ 70 ]).…”
Section: Interventions To Improve Sleep Health In Pediatric Pain Popu...mentioning
confidence: 99%
“…Table 1 provides examples of a paper sleep diary and several smartphone applications that can help teens track their sleep. Research shows that digital apps for managing sleep disturbances can yield significant reductions in depressive symptoms 71–73 …”
Section: Lifestyle Medicine: a Growing Disciplinementioning
confidence: 99%
“…Research shows that digital apps for managing sleep disturbances can yield significant reductions in depressive symptoms. [71][72][73] Recent studies, such as Sleep and Education: Learning New Skills Early (SENSE) by Blake and colleagues, 75,76 have demonstrated the efficacy of interventions based on Dahl and Harvey's approach 69 in group formats (Table 2) and shown that that this protocol can be adapted into school, clinic, or community settings.…”
Section: Sleepmentioning
confidence: 99%
“…Carmona et al [ 1 ] analyzed the effect of DOZE (Delivering Online Zzz's with Empirical Support) on adolescents and young adults. However, this was done only via feedback from the participants.…”
mentioning
confidence: 99%